Eco-Pedagogic Based on Eco-Theology: Strategies for Building Students' Spiritual, Social, and Cognitive Character - Nagiya, Nagiya; Zebua, Ali Marzuki (Fakultas Agama Islam Universitas Billfath, 2025)
This study examines the strategy of implementing Eco-Pedagogy based on Eco-Theology at Sekolah Alam Insan Rabbani Sungai Penuh to form spiritual, social, and cognitive character. With a qualitative approach to case studies, data is obtained through observation, interviews, and documentation. The data was analysed by thematic analysis through six stages. The results of the research show that Eco-Pedagogy based on Eco-Theology at Sekolah Alam Insan Rabbani (SAIR) Sungai Penuh can shape students' character spiritually, socially, and cognitively through various programs that are integrated with the values of Islamic teachings. The Green Latte program instills the value of responsibility, care, and gratitude to God for His creation; outing class activities enrich the learning experience by making nature and local wisdom a living source of learning; waste management and greening practices train ecological habits as well as ethical awareness; As well as the canteen-free school policy to foster environmental awareness from an early age through the reduction of plastic waste. Thus, the Eco-Pedagogy implementation strategy based on Eco-Theology at SAIR is not only oriented to knowledge transfer, but also forms a generation of khalīfah fil arḍ who have faith, knowledge, and ecological morals according to the mandate of Allah SWT.